The Value of Managing by Values: A Canadian Sport Organization Case Study - Shannon Kerwin; Joanne MacLean; Dina Bell-Laroche (Journal of Applied Sports Management, 2014)
The purpose of this study was an in-depth examination of the use of organizational values in the management practices of a nonprofit sport organization. Using a case study approach, interview (n = 13) and video (n = 5) data were examined to determine (1) the nature of employee involvement as it relates to the development of organizational values, (2) the process of enacting and communicating organizational values, and (3) the perceived link between the deliberate implementation of management by values and organizational performance within one national sport organization. Findings demonstrated the need for all employees and internal stakeholders to be involved in the value generation process. Furthermore, in order for organizational values to be understood and ‘lived' by personnel, values must be engrained into everyday human resource management sport policy and practice. Contribution to theory, as well as implications for sport practitioners and scholars are presented.
Keywords: management by values; organizational performance